THE INFLUENCE OF E-WALLET USE, FEAR OF MISSING OUT (FOMO), AND CONSUMPTIVE BEHAVIOR ON STUDENT FINANCIAL MANAGEMENT IN THE ERA OF DIGITAL LOANS - Ajeng Rizqi Ramandhani Putri; Aisha Hanif (Journal of Artificial Intelligence and Digital Economy, 2026)
Objective: This study aims to analyze the influence of digital wallet usage, Fear of Missing Out (FoMO), and consumerist behavior on students’ financial management in the era of digital lending. Method: This study employs a quantitative approach using primary data collected through a questionnaire distributed to active students at Muhammadiyah University of Sidoarjo. A total of 100 respondents were analyzed using multiple linear regression with the assistance of SPSS version 26. Results: The results indicate that the use of digital wallets has a positive and significant influence on students’ financial management, whereas Fear of Missing Out (FoMO) has a negative and significant influence. Additionally, consumptive behavior has a positive and significant influence on students’ financial management. Novelty: These findings suggest that the use of digital financial technology, social pressure, and experiences with consumptive behavior play a role in shaping students’ financial management in the era of digital lending.